Formulation and Evaluation of Rosuvastatin Calcium Polymeric Nanoparticles-Loaded Transdermal Patch - Mais Saadallah; Omar Hamid (University of Mosul, 2022)
Background: Transdermal drug delivery systems (TDDS) have been rapidly developed as a promising alternative to the oral delivery systems to provide controlled drug delivery and avoid the first-pass metabolism of drugs. Recently, various nanocarriers such as liposome and lipid nanoparticles have been used to enhance dermal and transdermal penetration of drugs. The aim of this study is to formulate and evaluate a polymeric nanoparticle (PNPs)-loaded transdermal patch of the antihyperlipidemic drug rosuvastatin. Materials and Methods: Rosuvastatin PNPs were prepared by nanoprecipitation method, and evaluated for particle size, zeta-potential and polydispersity index. PNPs-loaded patch and PNPs-free patch (control) of rosuvastatin were prepared by solvent casting method using hydroxyl polymethyl cellulose K15 (HPMC K 15) as film-forming polymer and polyethylene glycol 200 (PEG 200) as a plasticizer and evaluated for physical appearance, thickness, folding endurance, surface pH, in-vitro release and ex-vivo permeability. Results: The particle size, zeta-potential, and polydispersity index of rosuvastatin-loaded PNPs were 68.69 nm, - 7.5 mV, and 0.294, respectively. The prepared transdermal films showed acceptable appearance, thickness, and folding endurance as well as surface pH values. In vitro release study showed 65% and 82% cumulative release after 24 hrs for the polymeric nanoparticle-loaded patch and control patch, respectively. However. ex vivo permeation results showed that a significantly higher amount of rosuvastatin permeated via rat skin from the PNPs-loaded patch in comparison to the control patch (P-value ˂ 0.05). Conclusion: Rosuvastatin PNPs-loaded transdermal patch was successfully prepared and revealed promising releasing and permeation properties comparing to control patch.